2017
DOI: 10.1142/s233954781750008x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic network-based interrogation of rat liver metabolism following gastric bypass surgery featuring SWATH proteomics

Abstract: Morbidly obese patients often elect for Roux-en-Y gastric bypass (RYGB), a form of bariatric surgery that triggers a remarkable 30% reduction in excess body weight and reversal of insulin resistance for those who are type II diabetic. A more complete understanding of the underlying molecular mechanisms that drive the complex metabolic reprogramming post-RYGB could lead to innovative non-invasive therapeutics that mimic the beneficial effects of the surgery, namely weight loss, achievement of glycemic control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…While Sridharan et al reported proteomic analysis of a gastric bypass surgery rat model, the present study is, to our knowledge, the first to perform proteomics on several organs derived from the RYGB surgery and sham control mice, at several time points. Due to the large number of data sets and protein kinetics to analyze, we employed a high-dimensional clustering strategy XINA developed by our group, for the identification of RYGB-induced protein changes within the RL, BL, liver, and pancreas.…”
Section: Discussionmentioning
confidence: 91%
“…While Sridharan et al reported proteomic analysis of a gastric bypass surgery rat model, the present study is, to our knowledge, the first to perform proteomics on several organs derived from the RYGB surgery and sham control mice, at several time points. Due to the large number of data sets and protein kinetics to analyze, we employed a high-dimensional clustering strategy XINA developed by our group, for the identification of RYGB-induced protein changes within the RL, BL, liver, and pancreas.…”
Section: Discussionmentioning
confidence: 91%
“…In support of this possibility, hepatic Them2 levels were shown to be markedly reduced in rats following a gastric bypass surgery, which ultimately leads to decreased body weight and decreased hepatosteatosis. (35) The observation that THEM2 expression returned to basal levels in livers of NASH patients may reflect an inflammation-induced failure of this compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A modified RYGB procedure, Roux‐en‐Y esophago‐jejunal bypass was used as the surgical model in the experiment. 35 , 36 With the rat placed on a heating pad throughout the operation, anesthesia was induced with Isoflurane and Meloxicam given subcutaneously (5 mg/kg) immediately prior to the procedure. A 4 cm midline upper abdominal incision was made and Enrofloxacin (10 mg/kg) was injected intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%